2012
DOI: 10.4161/cc.20862
|View full text |Cite
|
Sign up to set email alerts
|

Chloroethylnitrosourea-induced cell death and genotoxicity: Cell cycle dependence and the role of DNA double-strand breaks, HR and NHEJ

Abstract: C hloroethylnitrosureas (CNUs) are powerful DNA-reactive alkylating agents used in cancer therapy. Here, we analyzed cyto-and genotoxicity of nimustine (ACNU), a representative of CNUs, in synchronized cells and in cells deficient in repair proteins involved in homologous recombination (HR) or nonhomologous end-joining (NHEJ). We show that HR mutants are extremely sensitive to ACNU, as measured by colony formation, induction of apoptosis and chromosomal aberrations. The NHEJ mutants differed in their sensitivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…2E: note the change of scale of the X axis). The death of MGMT-expressing cells at high dose CCNU treatment is likely the result of N-chloroethylations, which are less toxic than O 6 ClEtG [11]. Again, the expression of eATL in these cells had no impact on cell survival following CCNU treatment (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…2E: note the change of scale of the X axis). The death of MGMT-expressing cells at high dose CCNU treatment is likely the result of N-chloroethylations, which are less toxic than O 6 ClEtG [11]. Again, the expression of eATL in these cells had no impact on cell survival following CCNU treatment (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…However, induction of cell death following CNUs occurs in an MMR independent manner [9]. Thus, intramolecular rearrangement of the O 6 ClEtG adduct leads ultimately to the formation of an N1-guanine-N3-cytosine interstrand crosslink (ICL) [10], which blocks replication, resulting in collapse of replication forks and the formation of DSBs [11].…”
Section: Introductionmentioning
confidence: 99%
“…After washing with PBS, cells were incubated with ice-cold methanol for 10 min at −20°C. After three washing steps with PBS, to avoid unspecific binding, the blocking reagent (PBS + 0.25% Triton 100-X + 10% normal goat serum) was added for 1 h. The Rad51/yH2AX staining and evaluation was conducted as described [56]. After washing, nuclei were either stained with TO-PRO-3 (1:1000, 15 min; only for acquisition on LSM), or treated with 10 μL anti-fade medium (Vectashield) with DAPI (only for acquisition with Metafer system).…”
Section: Methodsmentioning
confidence: 99%
“…Epidemiological studies have shown that almost 80%-90% of human cancers are caused by the environment [1], being chemical pollutants the most important cancer-causing factors. Nitrosoureas are a class of DNA alkylating-agent anticancer drugs that include Chloroethylnitrosoureas (CENUs), such as 1-((4-amino-2-methyl -5-pyrimidinyl) methyl)-3-(2-chloroethyl)-3-nitrosourea (Nimustine, ACNU), 1,3-bis(2-chloroethyl)-1-nitrosourea (Carmustine, BCNU), 1-(2-chloroethyl)-3-cyclohexyl-L-nitrosourea (Lomustine, CCNU), 1-(2-chloroethyl)-3-(4-methlycyclohexyl) -1-nitrosourea (Semustine, MeCCNU) and 1-[N-(2-chloroethyl)-N-nitrosourea] ethylphosphonic acid diethyl ester (Fotemustine, FUNU) [2]. Previous studies have indicated that the cytotoxicity of CENUs is related to the formation of DNA interstrand crosslinks (ICLs) [3].…”
Section: Introductionmentioning
confidence: 99%